Mapping Sub‐Surface Structure of Thin Films in Three Dimensions with an Optical Near‐Field. Issue 6 (15th April 2019) - Fenwick, Oliver; Mauthoor, Soumaya; Cacialli, Franco
Abstract: Subsurface mapping is crucial to understanding many biological systems as well as structured thin films for (opto)electronic or photonic applications. A non‐invasive method is presented to map subsurface nanostructures from scanning near‐field optical microscopy images. The Bethe–Bouwkamp model is used to simulate imaging of buried nano‐objects or subsurface slanted planar interfaces, and it is shown how to determine their depth and size, or the interface inclination, from just one image. It is shown that the steep optical field gradient makes near‐field microscopy a particularly sensitive depth probe for thin films. Abstract : A non‐invasive method is presented to map subsurface nanostructures from scanning near‐field optical microscopy images. The Bethe–Bouwkamp model is used to simulate imaging of buried nano‐objects or subsurface slanted planar interfaces, and it is shown how to determine their depth and size, or the interface inclination, from just one image.